Build With Heart for People's welfare - Afrizal Tjoetra (Prodi Sosiologi FISIP Universitas Teuku Umar, 2015)
Typically, the development process set forth in the Medium Term Development Plan (Plan) district / city and province. Derivative development agenda in the form of a series of programs is reflected in the Budget (APBK) district / city and province. Considering the people as direct beneficiaries of development, so it will need public participation, both in the planning, implementation and monitoring and evaluation. If space is available and effective consultation in the district / city? This paper is intended to arouse stakeholders about the importance of the availability of space and the public consultation on the regional development strategy of the future. According to the theory, thedevelopment process can be criticized conducted through two main concepts, namely the modernization theory and dependency theory. The important lesson to be learned from the experience of 10 figures is the first elected regional leaders, for example, and honesty. Secondly, it turns out the area is able to take care of themselves. Third, there must be a rejection of the classical phenomenon of bureaucracy that is corruption, inefficiency, working without vision. Fourth, the intense communication is the key to success, and the fifth is impatient to hear the complaints of the people and work to achieve it.